Pemetaan jaringan perkhidmatan kebajikan kanak-kanak dalam jagaan institusi awam di Malaysia: Fragmentasi dalam jenis, corak, sistem dan agihan / Siti Hajar Abdul Rauf - Siti Hajar , Abdul Rauf (2017)
This study is about an effort to map out local child welfare network, in particular, the public institutional care. The study has three objectives. Firstly, to explore the child welfare network practices implementation. Second, to identify the antecedent factors that may hinder the involved agencies' capabilities to deliver conducive services that are consistent with the needs and rights of the children. Third, to develop social initiatives that can enhance the capacity of the existing child welfare network system. The study which is qualitative in its approach utilised Grounded Theory to gather data. A set of interview protocol was designed to guide a series of face-to-face and in-depth interviews among 30 respondents that come from 24 different agencies. The main finding of the study was the operations of the child welfare network system in Malaysia is in conflict with the mixed economy of care approach. The type of social network formed between agencies was formal. The networks tend to be one-way and directional, most of them operate through an intermediary agent, in the shape of symmetry relationship, and involved various agencies that work in a closed system. The study also concluded that the structural factors (i.e., legislative framework, the administration issuance, and geographic location) were the leading contributing factor that blocks the development of an integrated and conducive child welfare network in Malaysia. Three models; which are the Social Network Development Model, the Path of Least Resistance Model and the Innovative Model of Integrated Social Network were developed to respond to the empirical evidence. These models can be instrumental in developing an integrated child welfare network in Malaysia.